Answer:
x - 2y + 6 = 0
Step-by-step explanation:
Going from (-2, 2) to (4, 5), we see that x (the 'run') increases by 6 and that y (the 'rise') increases by 3. Thus, the slope of the line through these two points is m = rise / run = 3/6, or m = 1/2.
Starting with the slope-intercept formula y = mx + b, and using the x and y values from the point (-2, 2), we get
2 = (1/2)(-2) + b, or 4 = -2 + 2b, or 6 = 2b, or b = 3. Then the slope-intercept form of the desired equation is y = (1/2)x + 3. To obtain the standard form, we multiply all three terms of this result by 2, obtaining 2y = x + 6, or
x - 2y + 6 = 0